Examining the relationship between sprinting, drop jump, and vertical jump flight times in collegiate track athletes - Aldana, M., Gonzalez, M. P. Montalvo, S.; Dorgo, S. (International Journal of Exercise Science Conference Proceedings, 2025)
INTRODUCTION: Flight time during sprints, drop jumps, and vertical jumps is commonly used to evaluate athletic performance and neuromuscular function. While all three metrics reflect rapid force production, their relationships across different athletic movements remain unclear.